Whale Watching Tours as a Cultural Object in Fiction – Jojo Moyes’ Silver Bay - Marginean, Alexandra (European Scientific Journal, ESJ, 2021)
This paper starts from Jojo Moyes’ novel Silver Bay, looking at the way in which it presents tourism related to sea life watching and at aspects of people’s existence in a territory that has this type of potential. One of the aims is to raise awareness in what regards the specificity of such beach areas, in terms of not only opportunities, but also threats to sea ecosystems posed by excessive modernization driven by economic interests. Another aim is to interpret phenomena and attitudes presented in the story from a theoretical background, to make visible what mindsets the actions and behaviors in the novel manifest, from those discussed in intercultural, identity and cultural studies, which represent the academic theoretical approach in this research. Examples of these would be uncertainty (in)tolerance, masculine versus feminine cultures, dominant versus harmonizing (outer-directed) attitudes towards the environment. Moreover, certain potential iconoclastic interpretations, such as mystical exaggeration when it comes to interpreting whale communication may be elucidated. The analysis starts with the outline of the story and focal points, then pinpoints the significant role of sea life tourism in the novel. Afterwards, it goes on to set the explanatory background by looking at the polarity old-new and further superposed oppositions, to subsequently get to the description of whale watching, whale behavior and animal-related issues, and finally look into the metaphor of seeing the human being as a whale. The conclusions sum up the main findings: the fiction under the lens here is informative and raises awareness related to the abovementioned aspects (cultural identity and profiles, intercultural contrastive interpretations, typical forms of tourism, ecosystem preservation, irresponsible or illegal actions). They point out as well the relevance and placement of the topic in modern approaches on tourism, environmental concerns, sustainability and wildlife preservation in general.